Do brand image, product quality impact eiger bags repurchase intention? - Nurhadi, Nurhadi; Ramadania, Ramadania; Listiana , Erna; Barkah, Barkah; Rosnani, Titik (Institute of Computer Science (IOCS), 2024)
The aim of this research is to delve into the dynamics of consumer behaviour and its relationship with brand image, product quality, brand trust, and repurchase intention, focusing on the Eiger brand. The study employs a causal method, collecting data through questionnaires from 227 Eiger product users in Indonesia, utilizing purposive sampling techniques. Data analysis is conducted using Structural Equation Modeling (SEM) and AMOS 24, with measurements of brand image, product quality, brand trust, and repurchase intention variables. The findings indicate that brand image and product quality have a positive and significant impact on repurchase intention, with brand trust acting as a mediator that strengthens this relationship. This research provides valuable insights into understanding the contributions of brand image, product quality, and brand trust in influencing consumer repurchase intentions. Marketing and brand development strategies are recommended to maintain the competitive edge of Eiger in the outdoor equipment market. Research limitations include restricted variables and study subjects, suggesting that future research could expand analyses to external factors and comparisons with key competitors to enhance the understanding of consumer dynamics.